Work stress in the services sector - Angulo Rincón, Rosalba; Universidad Pontificia Bolivariana (Universidad Santo Tomás seccional Bucaramanga, 2014)
This research evaluates the response of job stress in 149 employees from the three offices of a courier company in eastern Colombia. The results show a moderate level of work stress with the presence of physiological symptoms, mainly associated to gastrointestinal problems, finding no differences in gender or marital status. Regarding organizational variables, a statistically significant correlation between the number of hours worked per week and stress level was found, unlike the hierarchical level variables and work place, where there was no correlation.